Ergonomic evaluation of postural assessment among “canting” batik workers - Norliana, Yusof; Rozimah, Yusof; Firoz @ Mohd Firoz, Ahmat Basri; Norhayati, Soin (2013)
This paper presents a study in batik industry with the objective of determining any musculoskeletal disorders (MSDs) among “canting” batik workers in Kuala Terengganu. The MSDs symptoms were identified through questionnaires modified from a Standardized Nordic Questionnaire (SNQ) and from observational techniques by using a postural analysis tool, Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA). The results of questionnaires revealed that MSDs occurred at a high rate which the highest rates of MSDs prevalence were reported in shoulders (64.5%). By assessing postural using the REBA score is 4 which are in medium risk level. However, there are another factors contribute to the existence of MSD such as prolong standing, repetitive movement and poor workstation design. These parameters are not taken into account in the RULA and REBA analysis. Thus, designing an ergonomic workstation may prevent awkward postures to provide a maximum comfort to the batik workers and consequently enhance the productivity